Migrant physicians' entrance and advancement in the Swedish medical labour market: a cross-sectional study - Linda Sturesson; Magnus Öhlander; Gunnar H. Nilsson; Per J. Palmgren; Terese Stenfors (BMC, 2019)
Abstract Background Worldwide, physicians are migrating to new countries and want to practise their profession. However, they may experience difficulties doing so. To optimise and accelerate their entrance into and advancement within the Swedish healthcare system, there is an urgent need to explore how they are currently doing so, as their competences should be put to use without any unnecessary delay. The aim of the study was to explore how migrant physicians with a medical degree from outside EU/EEA enter and advance within the medical labour market in Sweden and to identify perceived barriers and facilitating aspects in the process. The empirical findings are discussed in light of Bourdieu's concept symbolic capital as adapted in the Swedish medical field. Methods A cross-sectional study with a self-administrated questionnaire was disseminated. A sample of 498 migrant physicians were identified. Descriptive statistical analysis and qualitative thematic analysis were used to analyse the data. Results The response rate was 57% (n = 283). Respondents mainly found their first positions via spontaneous job applications, during internships, while participating in an educational intervention or via personal contacts. Perceived barriers to entering and advancing within the medical field in Sweden were mainly related to having a medical degree from and/or originating from another country, which could in turn represent discrimination and/or having one's competence undervalued as a result. Facilitating aspects included having or developing contacts in Swedish healthcare and gaining proficiency or fluency in the Swedish language. Conclusions When MPs find their first positions, the contacts they have developed appear to play a role, and when advancing in their positions, the active development of a variety of contacts seems to be beneficial. MPs experience a variety of barriers to entering and advancing within the field that could be related to discrimination. Many MPs perceived having their competences undervalued due to their origin or to being educated abroad. Based on the respondents' experiences, our interpretation is that MPs as a group are hierarchically positioned lower in the Swedish medical field than physicians trained in the country. Facilitating aspects included educational interventions, having contacts and developing language skills. For optimal entry into the labour market, it is vitally important for MPs to learn the new language and obtain a job or internship in the field as soon as possible.